Security Engineering for Vehicular IT Systems Improving the Trustworthiness and Dependability of Automotive IT Applications - Wolf, Marko (Vieweg+Teubner Verlag : Imprint: Vieweg+Teubner Verlag, 2009)
Even though most vehicular IT systems are indeed developed to face technical failures, they rarely consider a systematic malicious encroachment. However, in the degree that vehicular electronics are becoming software-driven, digitally networked and interactive IT systems, dependable security measures are essential to ensure driving safety and enable the automotive industry to achieve different legal requirements. Marko Wolf provides a comprehensive overview of the emerging area of vehicular security. Having identified potential threats, attacks, and attackers for current and future vehicular IT applications, the author presents practical security measures to meet the identified security requirements efficiently and dependably. The suggested implementations can contribute to ensure driving safety and protect the liability, the revenues, and the expertise of vehicle manufacturers and suppliers.